(untitled) (Bioagro, 2021)
In order to optimize machinery use, the application of herbicides has been performed at different times of the day and night. Therefore, knowledge about the pesticide that will be used and how the spray volume and time of application affect the effectiveness of the product is very important. Thus, the objective of this work was to study the influence of spray volume and different time of application on the control of Urochloa brizantha by different doses of glyphosate. The treatments were arranged in a 5 x 3 x 2 factorial scheme in a randomized block design with four replications. Five doses of glyphosate (0; 1080; 1440; 1800 and 2160 g∙ha-1∙a.e.), three times of application (morning, afternoon and evening) and two spray volumes (50 and 100 L·ha-1) were evaluated. A control assessment was performed at 21 days after application, in addition to the accumulation of dry matter and the leaf area index on the regrowth. A satisfactory control of the grass was obtained for applications performed in the morning and afternoon, without interference of the volume applied and the doses tested. Evening application reduces the effectiveness of glyphosate in Urochloa brizantha burndown.